Giant spontaneous epidermal cyst of the labia minora: a rare case report and literature review - Li, Xiang; Bai, Yuanyuan; Li, Jie; Li, Ruili; Fu, Jinying (Frontiers in Oncology, 2025)
BackgroundEpidermal cysts are benign subcutaneous masses resulting from the implantation of epithelial cells, following trauma or surgery. Giant spontaneous epidermal cysts of the labia minora are rare. To date, only 3 cases of epidermal cysts located in the labia minora have been reported worldwide.Case descriptionThis study presents a case involving an epidermal cyst of the labia minora with a diameter exceeding 8 cm, accompanied by endometriosis within an episiotomy scar and a concurrent Bartholins’s cyst. All lesions were surgically excised, successfully resolving the patient’s symptoms, and the final pathological diagnosis confirmed an epidermal cyst and endometriosis. The patient recovered well postoperatively, and follow-up at 3 months revealed no discomfort or complications.ConclusionThis case shows that spontaneous epidermal cysts of the labia minora are very rare and can enlarge rapidly over a short period. Prompt and thorough surgical excision is recommended to prevent recurrence and the potential for malignant transformation.